Penerapan Model Pembelajaran Berbasis Proyek Untuk Meningkatkan Hasil Belajar Matematika Siswa Kelas IV SD Inpres Kinilow - Paus, Julduz Ruland; Rorimpandey, Widdy H.F; Tambunan, Emi Napita (Peneliti.net, 2023)
This study aims to improve Mathematics learning outcomes in fourth grade students of SD Inpres Kinilow, through the application of the Project-Based Learning Model. This type of research uses Classroom Action Research (PTK) Model Kemmis and Robbin MC Taggart. Research subjects were fourth grade students with a total of 9 students, consisting of 5 male students and 4 female students. This research was conducted in two cycles and each cycle included four stages, namely; planning stage, implementation stage, observation stage, and reflection stage. Data collection techniques in this study are observation and tests. Based on the results of research in cycle I, only 4 students were complete while 5 were not complete or it can be said that the learning outcomes in cycle I were 44.44%. After implementing the action in cycle II, student learning outcomes have increased, where 9 students are complete. It can be said that the learning outcomes in cycle II are 100% and have reached the Minimum Completeness Criteria (KKM) of 75. Thus it can be concluded that by applying the Project-Based Learning Model with the material of the Perimeter of Flat Buildings can improve Mathematics learning outcomes in students in class IV SD Inpres Kinilow